Analysing the process of compulsory acquisition of land through the lens of procedural fairness: evidence from Scotland. Issue 1 (2nd January 2020) - Rao, Jyoti; Hutchison, Norman; Tiwari, Piyush
ABSTRACT: Compulsory acquisition of land is contested bitterly by affected landowners for various reasons including fairness in the compensation that is offered to landowners and fairness in the process that is followed in land acquisition by acquiring authorities. While there is a volume of research that has focussed on compensation, there is a paucity of literature analysing fairness in the process of land acquisition. This paper examines fairness in land acquisition using the case of Scotland, which is currently in the process of reforming laws and policies governing the compulsory acquisition of land. A primary survey was undertaken with stakeholders involved in a road project and information was analysed using 'qualitative content analysis'. This research identifies the gaps in the existing process of compulsory acquisition using the theoretical lens of 'procedural justice' with a strong focus on the social psychology dimension and argues for the incorporation of basic principles of 'procedural justice'. Fifteen major procedural gaps were identified, which include weak decision-making power of the members of the public in the identification and design of public projects; inadequate representation of objectors due to the high personal cost associated with representation in a public inquiry; time delays; information asymmetries and inefficient grievance management.